2013
DOI: 10.4103/0972-124x.119275
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic proteins: The anomalous molecules

Abstract: Bone is unique of all the tissues in the vertebrate organism. When injured, it heals by formation of new bone. Bone morphogenetic proteins (BMPs) are powerful inductors of the osteogenic activity during the embryologic bone formation phase and in cases of bone healing. They have proliferative effects on different cellular types, showing chemotactic properties and are able to induce mesenchymal cells differentiation into osteoblastic and chondroblastic line cells. Both primary cells and cell lines have been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…(13,14) BMPs act on the receptors of the cell membrane and play a significant role in regulating the growth, differentiation and apoptosis of various cell types including osteoblasts, chondroblasts, and nerve and epithelial cells. (15) To date, 20 types of BMP have been identified. The most fully studied for the regeneration of bone and cartilage are BMP-2 and BMP-7, but there are reports of active participation in osteogenesis and chondrogenesis and other BMP species.…”
Section: Discussionmentioning
confidence: 99%
“…(13,14) BMPs act on the receptors of the cell membrane and play a significant role in regulating the growth, differentiation and apoptosis of various cell types including osteoblasts, chondroblasts, and nerve and epithelial cells. (15) To date, 20 types of BMP have been identified. The most fully studied for the regeneration of bone and cartilage are BMP-2 and BMP-7, but there are reports of active participation in osteogenesis and chondrogenesis and other BMP species.…”
Section: Discussionmentioning
confidence: 99%
“…BMP-9, also known as growth differentiation factor 2 (GDF-2), is predominantly expressed in the central nervous system and liver during fetal development, and in the adult liver 102,103 . The ability of BMP-9 to induce the osteogenic differentiation of stem cells was found to be more potent than that of other BMPs 16 . Majumdar et al cultured hMSCs with BMP-2 and BMP-9, and found elevated expression of Col 2 mRNA and increased expression of aggrecan and cartilage oligomeric matrix protein, indicating chondrogenic differentiation of the cells.…”
Section: Bmp-9 For Cartilage Regenerationmentioning
confidence: 93%
“…After dimerization, these proteins are cleaved proteolytically at a consensus Arg-X-X-Arg site to generate mature dimers. BMPs consist of dimers whose chains are connected by disulfide bonds, and this dimerization is a prerequisite for bone induction 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Bone morphogenetic protein (BMP) is a protein that is essential for the normal repair of fractures [14]. Osteoblasts synthesize and secrete these BMP proteins, releasing them in large quantities into the bone matrix environment [15]. In total, there are over 20 BMP family proteins, and they are known to be able to strongly promote osteogenesis via direct stimulation of hMSCs leading to their differentiation [16,17].…”
Section: Introductionmentioning
confidence: 99%